Cohort Size and Youth Employment Outcomes - Newhouse, David (The World Bank, 2014)
This paper utilizes a cross-country panel of 83 developing countries to examine how changes in cohort size are correlated with subsequent employment outcomes for workers at different ages. The results depend on countries' level of development. In low-income countries, young adults that are born into smaller cohorts are less likely to work, but school attendance remains unchanged. In middle-income countries, young adults in smaller cohorts are less likely to be unemployed and more likely to work outside of agriculture. Neither pattern can be discerned among older adults, although the estimates are imprecise. In sum, reductions in cohort size are associated with moderate improvements in employment outcomes for youth in middle-income countries, but there is scant evidence that these improvements persist into adulthood